God's other book: the Qur'ān between history and ideology - Salama, Mohammad (University of California Press, 2024)
Introduction : primum non nocere -- Re-mapping Qur'ānic studies: histories and methods -- What is late antiquity and what does the Qur'ān have to do with it? -- Intelligence vs power : rhetorical dynamics in pre-Islamic poetry and the Qur'ān -- Poetic paganism and the monotheistic aesthetic -- Adab and the ethical authority of the Qur'ān -- The Qur'ān in context : monotheism and the birth of the un-Mimetic.